(untitled) (International Journal of Physiology, 2019)
Introduction Yogic practices can be considered to be a very good exercise for maintaining proper health and also has a profound effect on the lung functions of an individual. They are also used as psycho-physiological stimuli to increase the physiological functions and human performance. The present work is undertaken as there was no reported data on comparison of pranayama & suryanamaskar practitioners in various pulmonary endurance functions. Materials & Method The present study was conducted at MNR Medical College & Hospital, Sangareddy. The Institute Ethical Committee approved the study protocol. Informed consent was taken from all the subjects. The study was conducted with 80 subjects (aged between 18 to 20 years), under the supervision of a qualified yoga trainer. Inclusion Criteria: Medical students of age between 18–20 years, Only volunteers who are interested in practicing Yoga, Non alcoholic & non smokers. Exclusion criteria: Previous experience of yoga training and physically challenged persons. Results The MVV, 40 mm endurance and chest expansion were significantly increased (p<0.005) in the pranayama group (Group-II) and suryanamaskar group (Group-III). But the RR was significantly decreased (p<0.005) in pranayama (Group-II), suryanamaskar (Group-III) and combined group (Group-IV) than control group (Group-I), (p<0.005). Conclusion The regular practice of pranayama and Suryanamaskar practice induces more beneficial effects than physical exercise which mostly affects skeletal muscles. To meet the modern life style which is full of challenges and stress, an all-round personality development has become mediatory for the student, this aspect of relaxation and detachment is lacking in our education system and it is this new dimension (yoga) that needs to be added to the curriculum.